Spatiotemporal patterns of end-of-life passenger vehicle resources in China - DUAN Linlin, SONG Lulu, ZHONG Fanglei, WANG Wanjun, HAO Min, JIAN Xiaomei, CHEN Weiqiang (Ziyuan Kexue)
[Objective] The rapid growth of China’s passenger vehicle ownership has imposed tremendous pressure on resource supply and environmental carrying capacity. Analyzing the development trend of end-of-life resources in the passenger vehicle industry helps reveal the spatiotemporal evolution patterns of resource flows, while providing crucial data support and policy implications for optimizing the resource recycling system and promoting the sustainable development of the new energy vehicle industry. [Methods] Using the Gompertz model and dynamic material flow analysis, this study constructed a predictive framework for passenger vehicle ownership and end-of-life volumes across China’s 4 municipalities and 333 prefecture-level administrative regions. This framework systematically analyzed the spatiotemporal distribution patterns of different end-of-life passenger vehicle resources from 2001 to 2050. [Results] (1) China’s passenger vehicle ownership was projected to reach 450~640 million by 2050, showing significant regional disparities. Provinces such as Henan, Shandong, Hebei, and Guangdong had significantly higher ownership than other regions. (2) By 2050, the annual end-of-life passenger vehicles were estimated to reach 30.94~64.76 million, with a spatial shift observed from coastal cities to inland provincial capitals. Eastern coastal areas, the middle reaches of the Yangtze and Yellow Rivers, and southwestern regions would become concentrated end-of-life zones. (3) As new energy vehicles and hybrid electric vehicles became more prevalent, their end-of-life volumes would gradually exceed that of traditional fuel vehicles, leading to a substantial increase in the end-of-life volume of critical materials such as aluminum, copper, and power batteries. (4) Vehicle lifespan and ownership levels were identified as key driving factors affecting the end-of-life flows of passenger vehicles and automotive materials, exerting significant regulatory effects on the long-term resource metabolism trends. [Conclusion] The research findings provide a scientific basis for capacity planning in the resource recycling industry, formulation of regional differentiated policies, and construction of material recycling systems for new energy vehicles, thereby helping China achieve the “dual carbon” goals and circular economy transition.